Peningkatan Kemampuan Membaca dan Memahami Syair Khadamuddin Karya Aisyah Sulaiman Riau - Amanan; Hermansyah; Juswandi (BIDIK: Jurnal Pengabdian kepada Masyarakat, 2023)
Syair Khadamuddin is a literary work created by Aisyah Sulaiman Riau, a writer from the Riau archipelago. This literary work in ancient Malay, Syair Khadamuddin, tells the attitude and outlook on life as well as the loyalty of a wife to her husband. Syair Khadamuddin tells the story of the struggle of a woman named Siti Sabariah in realizing her loyalty as a wife who awaits the return of her husband, named merchant Khadamuddin. This service activity was held for PGRI High School students in Bukit Raya District, this activity is really needed by the Riau Provincial Government in the Reformation era, which has planned to foster and develop Malay culture and Malay culture (BMR). The arrival of the service team from the Faculty of Cultural Sciences, Lancang Kuning University is expected to be able to help the school and especially the PGRI Pekanbaru City High School students to get to know Riau Malay Culture, especially to improve their ability to read and understand Syair Khadamuddin by Aisyah Sulaiman Riau.